On the Sine-Gordon Equation with a Self-Consistent Source of the Integral Type - Khasanov, A.B.; Urazboev, G.U. (Журнал математической физики, анализа, геометрии, 2006)
It is shown that the solutions of the Sine Gordon equation with a source of the integral type can be found by the method of the inverse scattering problem for the Dirac type operator on the real line.